The U.S. Filibusters in Transnational Newspaper Discourses, 1855-1857 - Beer, Andreas (Current Objectives of Postgraduate American Studies, 2012)
The essay focuses on the transnational entanglements between the USA and Nicaragua in the mid-nineteenth century, when U.S. adventurers (so-called ‘filibusters’) started private invasions to the American isthmus. One embodiment of these entanglements was El Nicaraguense“, a bilingual newspaper published by the invaders and distributed in the USA and Central America. The article analyzes how the paper contributed to the incorporation of Nicaragua into the U.S. colonial realm.